Spatiotemporal Expression of GRP78 in the Blood Vessels of Rats Treated With 3-Nitropropionic Acid Correlates With Blood–Brain Barrier Disruption - Jin, Xuyan; Riew, Tae-Ryong; Kim, Hong Lim; Kim, Soojin; Lee, Mun-Yong (Frontiers in Cellular Neuroscience, 2018)
Glucose-regulated protein (GRP78) or BiP, a 78-kDa chaperone protein located in the endoplasmic reticulum (ER), has recently been reported to be involved in the neuroglial response to ischemia-induced ER stress. The present study was designed to study the expression patterns of this protein and the cell types involved in the induction of GRP78 expression in rats treated with the mitochondrial toxin 3-nitropropionic acid (3-NP). GRP78 immunoreactivity was almost exclusively localized to striatal neurons in saline-treated controls, but GRP78 expression was induced in activated glial cells, including reactive astrocytes and activated microglia/macrophages, in the striata of rats treated with 3-NP. In the lesion core, increased GRP78 immunoreactivity was observed in the vasculature; this was evident in the lesion periphery of the core at 3 days after lesion induction, and was evenly distributed throughout the lesion core by 7 days after lesion induction. Vascular GRP78 expression was correlated, both temporally and spatially, with infiltration of activated microglia into the lesion core. In addition, this was coincident with the time and pattern of blood-brain barrier (BBB) leakage, detected by the extravasation of fluorescein isothiocyanate-albumin, an established BBB permeability marker. Vascular GRP78-positive cells in the lesion core were identified as endothelial cells, smooth muscle cells, and adventitial fibroblast-like cells, in which GRP78 protein was specifically localized to the cisternae of the rough ER and perinuclear cisternae, but not to other organelles such as mitochondria or nuclei. Thus, our data provide novel insights into the phenotypic and functional heterogeneity of GRP78-positive cells within the lesion core, suggesting the involvement of GRP78 in the activation/recruitment of activated microglia/macrophages and its potential role in BBB impairment in response to a 3-NP-mediated neurotoxic insult.